The Influence of Marketing Mix on the Customer Satisfaction of Moringa Leaf Tea - Nikmah, Nisa Alfian; Setiadi, Agus; Ekowati, Titik (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
Marketing success is supported by the process of selecting the right product, good distribution channels, reasonable prices, and an effective promotion called Marketing Mix. Marketing Mix elements have to support each other in order to achieve marketing goals in order to achieve customer satisfaction. The objectives of this research are to analyze the Marketing Mix (product, price, place, promotion) and customer satisfaction of Moringa leaf tea and to analyze the effect of marketing mix on costumer satisfaction of Moringa leaf tea. The determination of the research location was based on the consideration that Blora Regency has a Moringa plantation and Moringa leaf tea processing factory. The research was conducted in January - February 2020. This research is a case study. The number of respondents was 110 respondents which selected using the quota method. The sampling method used was accidental sampling. Data collection was done by interview, observation and literature study. The data analysis used was descriptive analysis and multiple linear regression analysis. The results of the study are: product variables received unfavorable responses, price and place variables received good responses, promotion variables received bad responses and customers were satisfied. Product, price, place and promotion simultaneously affect customer satisfaction of Moringa leaf tea with a significant level of 0.000. The t-test results are significant on the price and place variables, while the product and promotion variables are not significant. Future research isexpected to analyze the level of customer satisfaction.